(untitled) (Bangladesh Agronomy Journal, 2015)
The experiment was laid down to identify mustard [Brassica juncea (L.) Czern & Coss] genotype tolerant to soil salinity in relation to shoot and total dry matter (root+shoot) plant-1, number of siliqua plant-1, number of seed siliqua-1, 1000-seed weight and seed yield plant-1. Four genotypes (BD 9080, BARI Sarisha16, BD 9109 and BD 9107) were evaluated at three levels of NaCl salinity, viz. 0 (normal), 50 and 100 mM. All of the mustard genotypes showed decreasing trend with respect to all of the above mentioned crop parameters with salinity over normal water and thee decreasing rate of the parameters was higher with the increasing salinity levels. Among the genotypes, BD 9080 showed the best performance with respect to above mentioned characters at all levels of salinity, while BD 9107 performed the poorest. Thus, genotype BD 9080 proved to be more tolerant to salinity than other genotypes. Bangladesh Agron. J. 2015, 18(1): 65-70